2013
DOI: 10.1111/ics.12077
|View full text |Cite
|
Sign up to set email alerts
|

Hypodermal delivery of cosmetic actives for improved facial skin morphology and functionality

Abstract: These results suggest that transbuccal formulations of nutraceutical grade cosmetics have potential to induce signal transduction pathways in facial hypodermis, resulting in anti-aging effects throughout all skin compartments, including dermal and epidermal layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
(49 reference statements)
2
17
0
6
Order By: Relevance
“…Cell# STD: values standardized to cell numbers (Cell#).myorelaxant platform such as the one described here may also be effective in relaxing this sphincter muscle and impacting perioral wrinkles.To the best of our knowledge, this is the first report of transoral modulation of facial muscles resulting in the visible improvement of the facial appearance.The benefits of the intraoral bioadhesive device described here extend beyond gummy smile remediation. Its grape seed/lecithin component provides fibroblast proliferation-stimulatory and MMP1/3 protein level inhibitory activities, in agreement with our previous gene expression findings 5. Such effects in the oral cavity may translate into stronger periodontal ligaments,10,11 if confirmed in clinical studies.…”
supporting
confidence: 91%
“…Cell# STD: values standardized to cell numbers (Cell#).myorelaxant platform such as the one described here may also be effective in relaxing this sphincter muscle and impacting perioral wrinkles.To the best of our knowledge, this is the first report of transoral modulation of facial muscles resulting in the visible improvement of the facial appearance.The benefits of the intraoral bioadhesive device described here extend beyond gummy smile remediation. Its grape seed/lecithin component provides fibroblast proliferation-stimulatory and MMP1/3 protein level inhibitory activities, in agreement with our previous gene expression findings 5. Such effects in the oral cavity may translate into stronger periodontal ligaments,10,11 if confirmed in clinical studies.…”
supporting
confidence: 91%
“…Overall, both HPLC and ATR-FTIR analyses allowed the identification and quantification of anthocyanins within the samples from the volunteers, demonstrating the penetration of the compounds as well as their lateral diffusion within the skin. Interestingly, hypodermal delivery has been reported for delivery of a proanthocyanidin-rich extract from grape seeds, a strategy to reach the epidermal and dermal skin layers, overcoming the issue of SC barrier crossing [ 195 ]. The quantification of anthocyanins within the epidermis and dermis is still a relatively unexplored topic of research, but it is of major importance considering the need to determine the required concentrations to observe the beneficial properties of anthocyanins in vivo, therefore this issue should be extensively explored in future works as it would provide very useful insights regarding the topical application of these molecules.…”
Section: The Role Of Bioavailability For Anthocyanins Photoprotectmentioning
confidence: 99%
“…Diffusion through the skin once past the rate-limiting SC should hypothetically arise much quicker and be independent of the vehicle composition [ 45 ]. The work by Bojanowski et al (2013) supports this hypothesis, who reported the hypodermal delivery of anthocyanins from grape seed extract through a transbuccal membrane when incorporated into soy phospholipids [ 46 ]. Grape skin extract was able to permeate into both the dermis and epidermis when applied to the hypodermal side of the skin.…”
Section: Resultsmentioning
confidence: 95%